205k views
5 votes
Evaluate.

(a - 2b)^2 when a = -4 and b = -1/2


25



9



-9



-25

Evaluate. (a - 2b)^2 when a = -4 and b = -1/2 25 9 -9 -25-example-1
User Hany Habib
by
5.8k points

1 Answer

6 votes
Substitute a=-4 and b=-1/2 into the expression:

((-4)-2(-1/2))^2

Remember, when we have a squared binomial, it expands; do not distribute the exponents! So, if we have (a+b)^2, we do not distribute the exponent of 2 to a and b. Instead, we expand the binomial: (a+b)(a+b). The logic of exponents applies because a number times itself x time forms the exponent n^x.

[(-4)-2(-1/2)][(-4)-2(-1/2)]

Now, use PEMDAS to simplify:

Parenthesis/brackets first:

Multiplication and division come before addition and subtraction:

(-4+1)(4+1)

Simplify the parenthesis, then multiply:

(-3)(-3)

-3•-3 = 9

So, the answer is: 9



User Ennael
by
5.4k points